Primary Hyperoxaluria Type 1 (PH1) Presenting With End-Stage Kidney Disease and Cutaneous Manifestations in Adulthood: A Case Report - Penelope Poyah (SAGE Publishing, 2021)
Rationale: Primary hyperoxaluria (PH) is a rare autosomal recessive disorder more commonly diagnosed in children or adolescents. Owing to its rarity and heterogeneous phenotype, it is often underrecognized, resulting in delayed diagnosis, including diagnosis after end-stage kidney disease (ESKD) has occurred or recurrence after kidney-only transplantation. Case Presentation: A 40-year-old Caucasian Canadian woman with a history of recurrent nephrolithiasis since age 19 presented with ESKD and cutaneous symptoms. She had no known prior kidney disease and no family history of kidney disease or nephrolithiasis. Diagnosis: A diagnosis of primary hyperoxaluria type 1 (PH1) due to homozygous splice donor mutation (AGXT c.680+1G>A) was made with kidney and cutaneous pathology demonstrating calcium oxalate deposition and ultrasound suggestive of nephrocalcinosis. Interventions: She was initiated on frequent, high-efficiency, high-flux conventional hemodialysis and oral pyridoxine. Lumasiran was added 11 months later, after she developed bilateral swan-neck deformities. Outcomes: After 14 months of high-intensity dialysis and 3 months of lumasiran, there have been no signs of renal recovery, and extra-renal involvement has increased with progressive swan-neck deformities, reduced cardiac systolic function, and pulmonary hypertension. The patient has been waitlisted for kidney-liver transplantation. Teaching Points: This case report describes an adult presentation of PH1. The case highlights the importance of timely workup of metabolic causes of recurrent nephrolithiasis or nephrocalcinosis in adults which can be a presenting sign of PH and genetic testing for PH to facilitate early diagnosis and treatment especially in the era of novel therapeutics that may alter disease course and outcomes. The case also demonstrates the value of testing for PH in adults presenting with unexplained ESKD and a history of recurrent nephrolithiasis or nephrocalcinosis due to implications for organ transplantation strategy and presymptomatic family screening.